Nonlinear optical propagation in a tandem structure comprising nonlinear absorption and scattering materials - BLAU, WERNER (My University, 2014)
Laser propagation in a tandem structure comprising carbon nanotubes and phthalocyanines is studied by Z-scan method. Due to the different mechanisms of the two materials, the laser beam can be attenuated with different absorptivities, by changing the sequence of light passing through each material. Numerical simulations considering the effect of path length and the change of nonlinear coefficient within each material are conducted for understanding the distribution of laser intensity in the tandem system and hence, fitting of the asymmetric Z-scan curves. The results are helpful for the design of nonlinear optical devices comprising multiple nonlinear materials and mechanisms.
PUBLISHED
Keywords: Laser propagation; Laser propagation